Relación entre el control interno y la rentabilidad de las empresas turísticas de la ciudad de Iquitos, durante el año 2022 - Velasco Dávila, Henrry Bradley (2023)
The objective of the research was to determine the relationship between internal control and the profitability of tourism companies in the city of Iquitos during the year 2022. For this, a non-experimental correlational quantitative study was carried out, and a questionnaire was applied to 92 tourism companies. from the city. The results showed a positive and significant relationship between internal control and the profitability of tourism companies. In addition, it was found that risk assessment and monitoring activities are also positively related to the profitability of tourism companies. In conclusion, the implementation of strong internal control policies and procedures, investment in technology and advanced monitoring tools, staff training, periodic risk assessments and regular monitoring activities can help tourism companies in the city of Iquitos to improve its profitability and long-term sustainability.